KEMUNGKINAN PEMANFAATAN LIMBAH JAMUR TIRAM (Pleurotus ostreatus, Jacq. Fr.) UNTUK BAHAN RESIN FENOL SEBAGAI PEREKAT KAYU LAMINASI - Djumhawan Ratman Permana; Bambang Prasetya (Universitas Sebelas Maret, 2014)
Abstract-Sawdust waste in the form of post- production of oyster mushrooms (Pleurotus ostreatus, Jacq. Fr.) presumably still contains a lot of short polymers of lignin derivatives can be chemically modified and becomes activated as a phenol resin adhesive laminated wood , MDF and particle board processing . Phenol resins produced with adhesive properties relative constancy is not much different would reduce dependence on the use of synthetic epoxy resin , while utilizing residual waste is wasted. In lamination technology is determined by factors other than adhesive bonded materials are also factors, gluing techniques, how to test and application materials. Characteristics of phenol resin as the adhesive is often influenced by factors fillers, developer, preservative and fire retardant materials. The use of phenolic resins in the gluing various materials are expected to result in the formation of a resin net structure on a regular basis. Keywords : Waste oyster mushroom (Pleurotus ostreatus , Jacq. Fr.), phenol resins, glue laminated wood